Study on the influencing factors of forest-based health and wellness services from the supply and demand perspective - Wei, Kunjing; Zhou, Geyao; Zhou, Xianfeng; Zhang, Yufang; Liao, Qiuyue (Frontiers in Public Health, 2025)
ObjectiveThis study investigates the key factors influencing the development of forest-based health and wellness (FHW) services in Guizhou Province, China, from both supply- and demand-side perspectives.MethodsA purposive sample of 242 staff members and 420 consumers from 17 FHW bases was surveyed between March and June 2024. Data were analyzed using binary logistic regression for supply-side factors and ordered logistic regression for demand-side determinants, following reliability and validity testing of the questionnaires.FindingsOn the supply side, the effectiveness of health management programs, adequacy of health facilities, and implementation of health education activities significantly affected service delivery. On the demand side, consumer satisfaction was shaped by instructor professionalism, perceived health benefits, the layout of leisure facilities, staff courtesy, and access to health product purchase channels.ConclusionTo advance the sustainable development of FHW, we propose a coordinated agenda across stakeholders. On the supply side, providers should strengthen the scientific rigor and implementation fidelity of health-management programs, upgrade and complete wellness infrastructure, and institutionalize routine health-education activities. On the demand side, priorities include enhancing the professional competence of wellness interpreters/guides and therapists; increasing consumers’ perceived health gains; optimizing the siting and accessibility of rest pavilions and related amenities; and improving courteous, patient-centered service as well as the availability and accessibility of health-product purchasing channels. For policymakers, stronger interdepartmental coordination is needed to support and enable the effective implementation of these measures.NoveltyThis study provides one of the first comprehensive analyses combining supply and demand perspectives in FHW services, offering evidence-based recommendations for policy, practice, and industry development in emerging health economies.